Influence of Restraint on Pore Structures and Air Permeability of Concrete Containing MgO-Type Expansive Agent - Wang, Aiguo; Sun, Daosheng; Deng, Min; Chen, Xiaoming; Zhang, Fengjun (Asian Journal of Chemistry, 2013)
The effect of restraint on pore structures and air-permeability of concrete containing MgO-type expansive agent was investigated in the paper. Pore structures of mortars in sided center and cubical center of concrete were analyzed using mercury intrusion porosimetry. The porosity and air-permeability of concrete were determined by method of evaporated water and Torrent permeability tester, respectively. The results show that restraint decreases porosity and pore size and improves pore size distribution of mortars in concrete containing MgO-type expansive agent. The improvement of pore structures in concrete matrix tends to increase density and decrease air-permeability of concrete containing MgO-type expansive agent.